Substitution, Complementarity, and the Residual Variation around Engel Curves - Theil, H. H.; Neudecker, H. (Review of Economic Studies, 1958)
H. H. Thell, H. Neudecker; Substitution, Complementarity, and the Residual Variation around Engel Curves, The Review of Economic Studies, Volume 25, Issue